1α,25-Dihydroxyvitamin D3 Promotes Angiogenesis After Cerebral Ischemia Injury in Rats by Upregulating the TGF-β/Smad2/3 Signaling Pathway - Zhang, Yajie; Mu, Yingfeng; Ding, Hongmei; Du, Bo; Zhou, Mingyue; Li, Qingqing; Gong, Shitong; Zhang, Fuchi; Geng, Deqin; Wang, Yanqiang (Frontiers in Cardiovascular Medicine, 2022)
Stroke is a disease with high morbidity, disability and mortality, which seriously endangers the life span and quality of life of people worldwide. Angiogenesis and neuroprotection are the key to the functional recovery of penumbra function after acute cerebral infarction. In this study, we used the middle cerebral artery occlusion (MCAO) model to investigate the effects of 1α,25-dihydroxyvitamin D3 (1,25-D3) on transforming growth factor-β (TGF-β)/Smad2/3 signaling pathway. Cerebral infarct volume was measured by TTC staining. A laser speckle flow imaging system was used to measure cerebral blood flow (CBF) around the ischemic cortex of the infarction, followed by platelet endothelial cell adhesion molecule-1 (PECAM-1/CD31) and isolectin-B4 (IB4) immunofluorescence. The expression of vitamin D receptor (VDR), TGF-β, Smad2/3, p-Smad2, p-Smad3 and vascular endothelial growth factor (VEGF) was analyzed by western blot and RT-qPCR. Results showed that compared with the sham group, the cerebral infarction volume was significantly increased while the CBF was reduced remarkably in the MCAO group. 1,25-D3 reduced cerebral infarction volume, increased the recovery of CBF and expressions of VDR, TGF-β, p-Smad2, p-Smad3 and VEGF, significantly increased IB4+ tip cells and CD31+ vascular length in the peri-infarct area compared with the DMSO group. The VDR antagonist pyridoxal-5-phosphate (P5P) partially reversed the neuroprotective effects of 1,25-D3 described above. In summary, 1,25-D3 plays a neuroprotective role in stroke by activating VDR and promoting the activation of TGF-β, which in turn up-regulates the TGF-β/Smad2/3 signaling pathway, increases the release of VEGF and thus promotes angiogenesis, suggesting that this signaling pathway may be an effective target for ischemic stroke treatment. 1,25-D3 is considered to be a neuroprotective agent and is expected to be an effective drug for the treatment of ischemic stroke and related diseases.